Biochemical and histological characterization of tomato mutants - Carolina C. Monteiro (Anais da Academia Brasileira de Ciências, 2012)
Biochemical responses inherent to antioxidant systems as well morphological and anatomical properties of photomorphogenic, hormonal and developmental tomato mutants were investigated. Compared to the non-mutant Micro-Tom (MT), we observed that the malondialdehyde (MDA) content was enhanced in the diageotropica (dgt) and lutescent (l) mutants, whilst the highest levels of hydrogen peroxide (H2O2) were observed in high pigment 1 (hp1) and aurea (au) mutants. The analyses of antioxidant enzymes revealed that all mutants exhibited reduced catalase (CAT) activity when compared to MT. Guaiacol peroxidase (GPOX) was enhanced in both sitiens (sit) and notabilis (not) mutants, whereas in not mutant there was an increase in ascorbate peroxidase (APX). Based on PAGE analysis, the activities of glutathione reductase (GR) isoforms III, IV, V and VI were increased in l leaves, while the activity of superoxide dismutase (SOD) isoform III was reduced in leaves of sit, epi, Never ripe (Nr) and green flesh (gf) mutants. Microscopic analyses revealed that hp1 and au showed an increase in leaf intercellular spaces, whereas sit exhibited a decrease. The au and hp1 mutants also exhibited a decreased in the number of leaf trichomes. The characterization of these mutants is essential for their future use in plant development and ecophysiology studies, such as abiotic and biotic stresses on the oxidative metabolism.